On the use of shape memory alloys for deployable passive heat radiators in space satellites. Issue 1 (February 2021) - Bacciotti, A; Bucchi, F; Frendo, F; Mameli, M; Perna, R; Filippeschi, S
Abstract: The present work presents a multifunctional structure for space engineering application part of the TOPDESS project, funded by ESA. The main aim of the project is the design of a thermal control device able to deploy through passive actuation. A combined device has been designed, made up of a Pulsating Heat Pipe (PHP) foldable heat exchanger and Shape Memory Alloy (SMA) wire. The deployment of the SMA wire is conceived to be controlled by thermal contact with the heat source and by conduction along the wire. Since the heat sources are lumped and the wire is subject to convection, a temperature gradient develops along the wire. A monodimensional mode able to predict the behavior of an SMA wire subjected to a spatial temperature gradient, is presented in this paper. The results show that the system can carry out folding and unfolding cycles with rotation angles greater than 80° only if the wire is subjected to uniform temperature distribution; in the case of temperature gradient, the achievable rotation angle is about 20°. The analysis states the feasibility of the actuation system, highlighting the critical technological aspects, to lay the groundwork for the future development of the whole system.